2008
DOI: 10.1007/s00276-008-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial anatomy of left lung: a study of multi-detector row CT

Abstract: Familiarity with prevailing pattern and variations in the bronchial tree is not only essential for the anatomist to explain bronchial variation in bronchial specimens, but also useful for guiding bronchoscopy and instructing pulmonary segmental resection. The purpose of this study was designed to demonstrate various branching patterns of left lung with 3D images, with special attention given to identify the major types at transverse thin-section CT. Two hundred and sixteen patients with routine thorax scans we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 16 publications
3
28
3
Order By: Relevance
“…However, supernumerary bronchi or an abnormal bronchus originating from the trachea are rare. A common variant branch, the subsuperior segmental bronchus in the inferior lobe, which branches from the common trunk of the basal segmental bronchi or stem bronchus supplying the basal segments, is found in 20-30% of left lungs and 50-60% of right lungs (Felson, 1973;Naidich et al, 1988;Wu et al, 1999;Ghaye et al, 2001;Zhao et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, supernumerary bronchi or an abnormal bronchus originating from the trachea are rare. A common variant branch, the subsuperior segmental bronchus in the inferior lobe, which branches from the common trunk of the basal segmental bronchi or stem bronchus supplying the basal segments, is found in 20-30% of left lungs and 50-60% of right lungs (Felson, 1973;Naidich et al, 1988;Wu et al, 1999;Ghaye et al, 2001;Zhao et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Normal variation and congenital anomalies of the bronchial tree have been studied extensively (Naidich et al, 1988;Wu et al, 1999;Ghaye et al, 2001;Yildiz et al, 2006;Zhao et al, 2009), and numerous variations have been observed in the lobar and segmental bronchial trees. However, supernumerary bronchi or an abnormal bronchus originating from the trachea are rare.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Zhao et al (2009) examined the bronchial anatomy of the left lung in patients (132 men, 84 women; mean age 47 year) who underwent conventional thoracic computed tomography scans for various reasons. At the level of the segmental bronchus in the upper and lower lobes, a bifurcation occurred in the majority of patients.…”
Section: Anatomical Variabilitymentioning
confidence: 99%